An Evaluation of Serum IgE and Th2-Associated Interleukins in Children With Uncomplicated and Complicated Appendicitis - Gudjonsdottir, Johanna; Roth, Bodil; Lovén, Gustav; Ohlsson, Bodil; Hagander, Lars; Salö, Martin (Frontiers in Pediatrics, 2022)
Background The pathogenesis of appendicitis is not understood completely and establishing a correct diagnosis can be clinically challenging. Previous investigations have shown an association between a T helper cell (Th)2-mediated inflammatory response, for example immunoglobulin E (IgE)-mediated allergy, and a decreased risk of complicated appendicitis. The present study aimed to evaluate differences in serum concentrations of IgE and Th2-associated interleukins (IL) in children with uncomplicated and complicated appendicitis. Method A prospective study including children <15 years with appendicitis. Blood samples were collected preoperatively at the time of clinical assessment at the Pediatric Emergency Department and analyzed for concentrations of serum total IgE and IL-4, IL-9, and IL-13. Associations with complicated appendicitis were evaluated through logistic regression adjusting for age, appendicolith, and symptom duration. Results 138 children with confirmed appendicitis were included. The median age was 10 (IQR 8–12) years, 87 (63%) were boys and 58 (42%) had complicated appendicitis. Children with complicated appendicitis had significantly higher concentrations of IL-9 and IL-13 compared to children with uncomplicated appendicitis. In the univariate logistic regression, high concentrations of IL-13 were associated with an increased risk of complicated appendicitis [OR 1.02 (95% CI 1.01–1.04) p = 0.005], which remained in the multivariate analysis [aOR 1.02 (95% CI 1.01–1.04), p = 0.01]. Serum concentrations of IgE, IL-4, and IL-9 did not significantly affect the risk of complicated appendicitis. Conclusion High levels of IL-13 seem to be associated with an increased risk of complicated appendicitis. This is incongruent with the hypothesis of an Th1/Th17-driven inflammation in this type of appendicitis.